Implementation of Cyber Public Relations in Building Organizational Image at Yayasan Haji Anif Medan (Pena Cendekia Insani, 2023)
The purpose of this study was to determine the application of cyber public relations in building organizational image at the Medan Haji Anif Foundation, Cyber Public Relations of the Haji Anif Foundation using various online media, Background of Yaysan Haji Anif's cyber public relations using cyber media, and cyber public relations strategies of the Haji Anif Foundation. The research method used is descriptive qualitative method. Data collection techniques using observation techniques, interviews and documentation. Data analysis techniques used reduction, data presentation and conclusion. The results of this study indicated that several strategies carried out by the Haji Anif Medan Foundation Cyber Public Relations were intensely analyzing websites periodically, handling crisis communications using social media by utilizing the convenience of reshare and two communication platforms. a more interactive direction, the process of implementing the Haji Anif Foundation's Cyber Public Relations in enhancing the positive image of the company utilizing online media as an appropriate means for publishing information about social activities, and the media used include; foundationhajianif.co.id website, social media such as Instagram and Facebook.